2020
DOI: 10.1177/0958305x20944035
|View full text |Cite
|
Sign up to set email alerts
|

Renewable and non-renewable energy consumption and economic growth in the US: A Markov-Switching VAR analysis

Abstract: We examine the relationship between renewable and non-renewable energy consumption and economic growth in the United States. While the regime-dependent Granger causality test results for the non-renewable energy consumption and economic growth suggest bi-directional causality in both regimes, we cannot validate any causality between renewable energy consumption and economic growth. The US meets its energy demand from non-renewable sources; as such, renewable energy consumption does not seem to affect economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 60 publications
(92 reference statements)
2
20
0
1
Order By: Relevance
“…Moreover, the research of Fu et al ( 2021 ) in selected African countries on the determinants of CO 2 using a dataset from 1980 to 2014 and the ARDL approach found that the effect of NREN on CO 2 was positive, while the impact of REN on CO 2 was negative. Similarly, Cevik et al ( 2021 ) scrutinized the energy use-CO 2 relationship in the USA utilizing Markov-Switching VAR from 1980 to 2018. The outcomes from the study disclosed that the nonrenewable impact on CO 2 was positive, while the influence of renewable influence on CO 2 was negative, suggesting that renewable energy helps in reducing degradation of the environment in the USA.…”
Section: Synopsis Of Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the research of Fu et al ( 2021 ) in selected African countries on the determinants of CO 2 using a dataset from 1980 to 2014 and the ARDL approach found that the effect of NREN on CO 2 was positive, while the impact of REN on CO 2 was negative. Similarly, Cevik et al ( 2021 ) scrutinized the energy use-CO 2 relationship in the USA utilizing Markov-Switching VAR from 1980 to 2018. The outcomes from the study disclosed that the nonrenewable impact on CO 2 was positive, while the influence of renewable influence on CO 2 was negative, suggesting that renewable energy helps in reducing degradation of the environment in the USA.…”
Section: Synopsis Of Related Studiesmentioning
confidence: 99%
“…Nations are moving to renewable energy for all these ecological reasons. Renewable energy is anticipated to overtake coal in power output by 2025, and renewable sources will contribute 50% of the global production of electricity by 2050 (Cevik et al, 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A general view puts forth the notion that the most important variables affecting carbon emissions are economic growth and energy consumption. 1821 Therefore, the second research direction involves the causal relationship test between CO 2 emissions and economic growth. Results show ambiguity, as There have been no unified conclusions about the connection between CO 2 emission and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The bootstrap based LR test consists of four steps (Cevik et al, 2020). The standardized residuals from the linear model are obtained in the first step.…”
Section: B Econometric Frameworkmentioning
confidence: 99%